2013
DOI: 10.4236/wjns.2013.34036
|View full text |Cite
|
Sign up to set email alerts
|

Novel object recognition is not affected by age despite age-related brain changes

Abstract: Age-related memory impairments show a progressive decline across lifespan. Studies have demonstrated equivocal results in biological and behavioral outcomes of aging. Thus, in the present study we examined the novel object recognition task at a delay period that has been shown to be impaired in aged rats of two different strains. Moreover, we used a strain of rats, Fisher 344XBrown Norway, which have published age-related biological changes in the brain. Young (10 months old) and aged (28 months old) rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that aged rodents are not impaired in their ability to recognize and preferentially explore novel objects when delays between sampling and testing are short (2–15 min) ( Burke et al, 2010 ; Bergado et al, 2011 ; Arias-Cavieres et al, 2017 ) but are impaired relative to young adult animals with long-term delays ( Cavoy and Delacour, 1993 ; Lukaszewska and Radulska, 1994 ; Pietá Dias et al, 2007 ; Burke et al, 2010 ; Aktoprak et al, 2013 ; Arias-Cavieres et al, 2017 ; Weiler et al, 2021 ), similar to animals with hippocampal inactivation ( Hammond et al, 2004 ), perirhinal lesions ( Ennaceur and Aggleton, 1997 ; Kesner et al, 2001 ), and aged human subjects ( Davis et al, 2003 ). This suggests that the observed age-related memory impairment is due to memory load rather than impaired ability to perceive differences between objects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that aged rodents are not impaired in their ability to recognize and preferentially explore novel objects when delays between sampling and testing are short (2–15 min) ( Burke et al, 2010 ; Bergado et al, 2011 ; Arias-Cavieres et al, 2017 ) but are impaired relative to young adult animals with long-term delays ( Cavoy and Delacour, 1993 ; Lukaszewska and Radulska, 1994 ; Pietá Dias et al, 2007 ; Burke et al, 2010 ; Aktoprak et al, 2013 ; Arias-Cavieres et al, 2017 ; Weiler et al, 2021 ), similar to animals with hippocampal inactivation ( Hammond et al, 2004 ), perirhinal lesions ( Ennaceur and Aggleton, 1997 ; Kesner et al, 2001 ), and aged human subjects ( Davis et al, 2003 ). This suggests that the observed age-related memory impairment is due to memory load rather than impaired ability to perceive differences between objects.…”
Section: Discussionmentioning
confidence: 99%